A Novel Architecture based on Deep Learning for Scene Image Recognition - Shri Kumar, Bhavesh; Naren, J.; Vithya, G.; Prahathish, K. (International Journal of Psychosocial Rehabilitation, 2024)
Scene recognition is a work of great significance in computer vision and artificial intelligence. Certainly, it is difficult due to various factors like cluttered image, poor separation of boundaries in between the scene objects, bad lighting, etc. Hence, the topic receives huge research attention. In this paper, the various applications using Scene Recognition and the various techniques that are incorporated to classify, feature extract and cluster scene images are reviewed and a method based on DNN is proposed.